First european results of shape-sensing robotic-assisted bronchoscopy - Brock, Judith; Dittrich, A. Susanne; Kontogianni, Konstantina; Heußel, Claus Peter; Klotz, Laura Valentina; Winter, Hauke; Schellenberg, Mavi; Keppler, Ulrich; Herth, Felix (Respiration, 2025)
Introduction: Shape-sensing robotic-assisted bronchoscopy (ssRAB) was shown to be superior in diagnosing peripheral pulmonary nodules (PPNs) compared to conventional bronchoscopy. Although RAB is established in the USA since 2019, the ION™ Endoluminal System was not CE marked in Europe until 2023. Methods: The first prospective European single-center, premarket study, conducted between 2022 and 2023, assessed the diagnosis of PPNs with ssRAB, using the ION™ Endoluminal System. Patients with suspected lung cancer or metastasis, PPNs of 1-3 cm, and ≥3 airway generations out were included in this study and followed up for up to 6 months. The primary outcome was the rate of tool-in-lesion (TIL), confirmed by mobile cone-beam computed tomography or with malignant index biopsy finding. Secondary outcomes included procedural characteristics, diagnostic yield, and adverse events. Results: A total of 43 patients with a mean nodule size of 19.2 × 16.9 × 15.8 mm, a mean distance of 17.4 ± 15.5 mm to the pleura, and mean 6.6th generation of airway were analyzed. TIL was achieved in 90.7% of all cases. Strict diagnostic yield was 67.4% and sensitivity for malignancy was 78.6%. No pneumothorax and no adverse events were reported outside of 3 cases of Nashville ≤2 bleeding. Predictors for successful diagnosis were the inner or middle third location (OR: 4.19, p = 0.039), CT bronchus sign (OR: 4, p = 0.044), and distance from pleural wall (OR: 1.05, p = 0.048). The lower lobe location (OR: 0.06, p < 0.001) was associated with nondiagnostic cases. Conclusion: The first European cases show ssRAB is a safe procedure with promising results for enabling diagnosis of PPNs.